Membangun Keunggulan Bersaing di Era New Value Economy - Sandra Sunanto (The Winners, 2005)
In the new value economy era company is demanded to give more innovative offering to the market. Value becomes the most important thing as the part of company’s offering. The unique of product, store, services and brand are part of company’s uniquevalue propositions. The brand value chain pushes the brand to become a tool that can create the company’s competitive advantage. This concept needs commitment and change the way of thinking from the all of company’s members. The value oriented brand system is becoming one distinctive alternative for company to build its competitive advantage in the new value economy era.